Young People's Early Offending: The Context of Strained Leisure Careers. (May 2014) - Corr, Mary-Louise
Criminology has witnessed a growth of interest in the later stages of criminal careers with less attention given to providing an understanding of the onset of offending which goes beyond identifying the precipitative or 'risk' factors. Drawing on findings from a study of young people's offending careers in Ireland, this article provides a contextualized understanding of the onset of crime located in young people's biographical experiences and transition through youth more specifically. It focuses on one particular dimension of this process, suggesting that early offending can be understood as emerging in the context of strained leisure careers. The findings also highlight the close interaction between the development of young people's leisure careers and their experiences of the local neighbourhood and social networks. It argues that responses to the early stages of youth offending must widen their focus from the individual to incorporate an understanding of broader socio-economic and cultural contexts.